Urban value proposition of industrial built heritage - Geevers, Kees (A+BE | Architecture and the Built Environment, 2014)
This dissertation is the reflection of the research study into urban planning structures of historic industrial complexes. The study’s aim has been to promote recognition and acknowledgement of these structures as the carriers of cultural-historical values in spatial transformation. Apart from object value, industrial heritage also has ensemble value. Being “the field of study into the material culture remains of industrial production and technology”, the field of Industrial Archeology offers the opportunity to gain further knowledge of the nature and background of industrial spatial planning. Given the current focus on cultural- historical values in spatial planning and the fact that the strategy of ‘conservation through development’ has found widespread recognition and application, this dissertation has set out to arrive at concrete definitions and instrumentation of reuse and transformation in urban planning. The study is based on existing sources of knowledge which allowed two spheres of human involvement and endeavour to be connected. The first is building archeological research that has been put into operating guidelines and has developed into a considerable volume of knowledge and experience which has shaped the practice of planning as well as the teaching of design. This field of knowledge represents the cultural- historical component of the study. In addition there is the domain of spatial planning discipline. The knowledge acquired in this area has been brought together in a series of four publications under the heading “The Fundamentals of Urbanism in the Perspective of the Twenty-First Century”. This, too, incorporates a considerable volume of knowledge and experience, which has been been laid down in publications classified on the basis of a planning-level approach to distinguish aspects of design, theory, law and programming. This planning-level approach allows for a structured and differentiated way to tackle industrial urbanization at the level of its composing parts. One case study lies at the heart of this dissertation’s research. It’s that of the former industrial estate of Philips Strijp-S at Eindhoven, The Netherlands. In selecting this location aspects of size and range have been taken into consideration. A decisive factor in its selection, no doubt, has been the amount of attention generated by and for the transformation itself. Prominent administrative and professional parties have gone through a process of research and planning that has been extensively documented. As a result, a fair account of the facts could be made. In it the administrative and societal contexts are closely connected with both research and design of the transformation. Urbanization archeological research is conducted under two denominators: research and value assessment. In order to reach a cultural-historical valuation, this study includes reference research into the city of Zlín, the cradle of Thomas Bat’a’s shoe industry in the former Czechoslovakia, for three reasons. There are major similarities between Philips and Bat’a in momentum, industrial ambition and innovative fundamental attitude first at the personal level of the entrepreneurs, secondly at the company level of industrialised production, and thirdly at the level of spatial and societal conditions. Philips started as a light-bulb factory located at Emmasingel, now part of the city centre of Eindhoven. When the company expanded with the addition of its own glass factory, it marked the beginning of the Strijp-S industrial estate. The Strijp-S study continues to concentrate on the most important period in terms of urbanization history, from the start of construction at the site in 1916 up to the fifties. At that point the company’s expansion involved the outplacement of essential company parts. The year 1951 marks the completion of the Strijp-S era, because it was then when the company’s spatial situation was documented by means of an ‘enriched’ map of the factory’s industrial estate. The ‘bottom-up’ approach of the Guidelines for Building Archeological Research (2009) has been adopted for the research study into the history of Strijp-S construction and use. The origin and expansion of the spatial planning structure of the Strijp-S estate have been shown in connection with the development of the company itself. The innovative fundamental attitude that led to the diversification of production (from light bulbs to a broad range of electrical appliances) in the first half of the twentieth century turned out to have been the breeding ground for an equally innovative architectural and urban-planning establishment of spatial and societal conditions in the interest of the company and the city of Eindhoven as a whole. Narrowly tracing the growth stages of the estate has brought into focus the elementary parts of the kind of spatial and programmatic structure which in the course of time have developed into typological constructs. Knowledge of Zlín and Bat’a helped to identify the factors that contributed to the success of the Philips company organization as inspired by American examples, such as Daylight Factories, Integrated Industry and Company Town. Thomas Bat’a built nearly a hundred daylight factories in and around Zlín, a city with a population of 40,000. Here the Integrated Industry did not only involve the production of shoes but also the ‘production’ of the entire city, in recent literature praised as a model company town. There was a substantial connection with Philips as appeared from the decision in the twenties to locate the Dutch branch of Bat’a in the town of Best, not far from Philips. In addition, an architectural-historical connection came to light between Zlín and Tony Garnier’s plan for a ‘Cité Industrielle’, which he had already developed in 1904, but was not published until 1917 under the title Une Cité Industrielle in reference to Lyon. Garnier’s spatial concept was virtually copied for Zlín. Although there is no irrefutable proof, a connection between Strijp-S and Garnier’s work is not unlikely in view of the personal connection between Anton Philips and Thomas Bat’a. On the basis of existing knowledge of the Zlín reference case a value assessment has been made for Strijp-S. As an extension of the editorial part, a values map has been designed to serve as an instrument for the urban spatial developer. Much was to be gained from a cartographer’s point of view since existing maps are wide of the mark. Maps that seemed to fit into the framework of the archeological urban approach turned out to be focused on the object too much, to be of varying levels of abstraction and to be unsuitable as blueprints for development. Elementary parts of the spatial and programmatic development of the urbanization of Strijp-S could be identified and inserted into the plannning-level structure of “The Fundamentals of Urbanism”. As a result a classification of concepts in the interest of cartografical representation was possible. The urbanization archeological values map that has been produced in this way has all the hallmarks that are needed for it to serve as a blueprint for the development process: topographical precision, abstract representation of spatial structures and distinguishing features according to cultural- historical values. The transformation history of Strijp-S is characterized by a process in which urban- planning research has not always been connected to development in the proper chronological order. In a review of that process and the development plans that have been made for Strijp-S in recent years by means of the set of instruments developed, it has been found that there is much left to be desired about those plans in terms of the cultural-historical values of the industrial spatial planning of the estate.